Building and locational characteristics’ quality of purpose-built offices in Malaysia and their relationship with rentals / Edie Ezwan Mohd Safian - Mohd Safian, Edie Ezwan (2015)
Purpose-built office (PBO) market in Malaysia has shown positive developments and increasing level of competitiveness. Many characteristics of PBO were unveiled by virtue of recent studies, market demand, and technology growth and new guidelines/ standards in order to fulfil the property market participants’ need. As a result, the characteristics of Malaysia’s PBO have become more complex. The increasing complexity of characteristics would entail greater needs on their influence on the rental levels of the PBO space. Nevertheless, there is a lack of research in the country that had actually studied in detail the influence of both the building and locational characteristics on rental levels alone in Malaysia. Therefore, the purpose of this thesis is to establish the building and locational characteristics’ quality of PBO and their relationship with rentals in the Malaysia’s office property market. Integral to achieve this objective, various characteristics that cover all fields are grouped under eight categories. Delphi Method has been selected as a reliable qualitative method according to the local context in developing building and locational characteristics of ranking through the eyes of local expert panels that can deliver guidance to researcher in recognising the quality of each characteristics of PBO in the local environment. In line with the gap of knowledge in relation to the need to adopt a more consumer oriented approach and the utilisation of high level spatial technology to refine the measurement of variables, modification and improvement based on the current method that is Building Quality Index (BQI) has been applied into this research. Building and Locational Quality Index (BLQI) was introduced as a unique approach whereby it emphasised on observation method for the quality level of each of the characteristics of PBO in detail. It is a comprehensive method that can combine the data between weightage of importance and weightage of score for each PBO characteristics. Analytical Hierarchy Process (AHP) method analysed the weightage of importance based on the occupants’ perception towards PBO. An analysis through a detail observation was done based on previous developed building and locational characteristics’ ranking of PBO. There are differences on PBO characteristics that became the variables, building characteristics of PBO that have been measured through building inspections and an informal interview whereas for locational characteristics of PBO, Geoinformation System software measured the distance and radius precisely. BLQI method also takes into account the subjectivity and objectivity in making a measurement. Hence, by having quality index for building and locational characteristics of PBO, regression analysis was applied to analyse the relationship between these characteristics’ quality of PBO and rental. Moreover, in benefiting from a plethora of variables, several areas in Kuala Lumpur were selected to provide the data on PBO. The study was successful in identifying the relationship of each characteristics of PBO with rental which they have given different results in each study area. Thus, this study is expected to provide insights to the property market participants in improving the performance of the office property market particularly in Malaysia so that it can compete in the international arena.